Effect of Co-60 gamma irradiated chitosan and phosphorus fertilizer on growth, yield and trigonelline content of Trigonella foenum-graecum L. Issue 3 (July 2015) - Dar, Tariq Ahmad; Uddin, Moin; Khan, M. Masroor A.; Ali, Akbar; Mir, Suhail Rasool; Varshney, Lalit
Abstract: Natural marine polysaccharides such as chitosan, sodium alginate and carrageenan; after depolymerization by different techniques, have shown promising plant growth promoting and other biological activities. Chitosan after irradiation with Co-60 gamma-rays have proven to be a miraculous plant growth promoter in different plants. Trigonelline; an anti-diabetic compound is obtained mainly from the seeds of Fenugreek ( Trigonella foenum-graecum L.). Trigonelline counteracts diabetes mellitus (DM) through the operation of the mechanisms of insulin secretion, modulation of β-cell regeneration and stimulation of activity of glucose metabolism related enzymes. Considering the medicinal importance a pot experiment was conducted to investigate the effect of foliar application of Co-60 gamma irradiated chitosan (IC) with soil applied phosphorus supplement on growth, biochemical and quality attributes of fenugreek. Four concentrations of irradiated chitosan were used (0, 40, 80 and 120 mg L −1 ) individually as well as in combination with single dose of phosphorus 40 kg ha −1 . Un-irradiated chitosan (UN) 40 mg L −1 and de-ionized water were used as control. IC significantly affected almost all the parameters including seed yield, trigonelline content and trigonelline yield. There were 10 treatments and among all, P40 + IC 40 mg L −1 proved to be the best, which increased total alkaloid content by 34.9%, seed yield by 125.4%, and trigonelline content by 17.8%. Contents of photosynthetic pigments and activity of nitrate reductase, carbonic anhydrase enzymes were also significantly enhanced.